Ribonucleotide Reductase Inhibitors: A New Look at an Old Target for Radiosensitization - Chapman, Tobias; Kinsella, Timothy J. (Frontiers in Oncology, 2012)
Ribonucleotide reductase, the rate limiting enzyme in the synthesis and repair of DNA, has been studied as a target for inhibition in the treatment of cancer for many years. While some researchers have focused on ribonucleotide reductase inhibitors as chemotherapeutic agents, particularly in hematologic malignancies, some of the most promising data has been generated in the field of radiosensitization. Early pre-clinical studies demonstrated that the addition of the first of these drugs, hydroxyurea, to ionizing radiation produced a synergistic effect in vitro, leading to a large number of clinical studies in the 1970-80’s. These studies, mainly in cervical cancer, initially produced a great deal of interest, leading to the incorporation of hydroxyurea in the treatment protocols of many institutions. However, over time, the conclusions from these studies have been called into question and hydroxyurea has been replaced as the standard of care for cervical cancer. Over the last ten years, a number of well-done pre-clinical studies have greatly advanced our understanding of ribonucleotide reductase as a target. Those advances include the elucidation of the role of p53R2 and our understanding of the temporal relationship between the delivery of ionizing radiation and the response of ribonucleotide reductase. At the same time, new inhibitors with increased potency and improved binding characteristics have been discovered, and pre-clinical and early clinical data look promising. Here we present a comprehensive review of the pre-clinical and clinical data in the field to date and provide some discussion of future areas of research.